The analysis of the influence of a graphical user interface's design on the number and time of website visits - Wasyluk, Izabela; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2019)
Article presents how working on a website's design can significantly influence business benefits deriving from running the site, and if it can reduce the expenses connected with investing in advertisements. The research was based on the website of an operating English language school with real needs to increase user conversion. During the tests, specific information concerning visits was collected, including the length of a visit and the number of visits paid to particular subpages. Special attention in this research was paid to changes on graphic elements such as size, colour or location on the website.